2020
DOI: 10.1007/s10067-020-04970-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and network meta-analysis of current and investigational treatments for active ankylosing spondylitis

Abstract: Objective To compare the relative efficacy of current and investigational biologic and oral small molecule (OSM) treatments for active ankylosing spondylitis (AS). Methods A systematic literature review was conducted to identify all phase 2/3 randomized trials of interest in patients with AS. Outcomes assessed were ≥ 20% improvement in the Assessment of Spondyloarthritis International Society Criteria (ASAS20) and change from baseline in Bath Ankylosing Spondylitis Functional Index (BASFI) and C-reactive prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
1
21
0
4
Order By: Relevance
“…Several recent ITC studies have compared the effectiveness of biologic therapies in AS at time points varying from 6 to 24 weeks of treatment, and have generally concluded that no specific agent is superior to others [8,30,31,[35][36][37][38]. At the substantially longer treatment time points included in the present PSM study, GOL IV was found to be significantly more efficacious than IFX in terms of ASAS20 response.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Several recent ITC studies have compared the effectiveness of biologic therapies in AS at time points varying from 6 to 24 weeks of treatment, and have generally concluded that no specific agent is superior to others [8,30,31,[35][36][37][38]. At the substantially longer treatment time points included in the present PSM study, GOL IV was found to be significantly more efficacious than IFX in terms of ASAS20 response.…”
Section: Discussionmentioning
confidence: 78%
“…Though MAIC is an acceptable approach, the absence of IPD from one of the trials necessitates the use of a broader IPD population compared with the comparator study. Weighting techniques are required to align patient populations, which may result in a smaller effective sample size [30]. In contrast, the PSM methods used in the present study use matching methods that are more intuitive to clinicians and decision makers compared with weighting methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В условиях отсутствия прямых сравнений основными источниками доказательств становятся сетевой метаанализ и непрямые сравнения. Вместе с тем, опубликованные в настоящее время систематические обзоры и метаанализы [13][14][15][16] не совсем релевантны для российской популяции пациентов, поскольку в них оценивались ГИБП или режимы их введения, не зарегистрированные в Российской Федерации (РФ). Кроме того, в них отсутствуют данные о препаратах, зарегистрированных и обращающихся только на территории России, к числу которых относится иИЛ-17 НТК.…”
Section: Introductionunclassified
“…Even when a fracture is clinically suspected, the diagnosis can be di cult on the basis of X-ray alone, given the highly abnormal spinal structure in patients with AS, including ossi ed ligaments, surrounding osseous proliferation, poor outlining of the disc space, and osteoporosis [7,8]. Moreover, the diagnosis may be complicated by the presence of long-standing pain and the application of corticosteroid therapy and NSAIDs, which can mask the acute fracture symptoms [9]. In a study by Caron et al, 30% of the AS cases with spine fractures did not initially obtain correct diagnosis [10].…”
Section: Introductionmentioning
confidence: 99%